Nuansa dan Simbol Sufistik Puisi-puisi Karya Ahmad Mustofa Bisri - Kundharu Saddhono; Haniah Haniah (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
This article focuses on the problem of Sufism which exists in pesantren’s poetry. The pesantren’s poetry has certain characteristics as it is written by poet whose educational background is pesantren. The values of Sufism will be reflected directly or indirectly into a poem written by a poet educated in pesantren. This what makes the poems produced from pesantren differ from that of other general poems. The specific features of the pesantren’s poems become interesting object to investigate. Focusing on written references this study employs heurmeneutical approach. It takes also the socio-cultural aspect into account. The use of this approach is based on an assumption that there should be tightly close relationship between the poem and the educational background of its writer. A poem exists within no cultural emptiness. At this point, the culture of pesantren that shaped a poet will influentially colour up the poem he/she produced. Based on hermeneutical approach coupled with socio-cultural aspect this study attempts to describe interesting side of Sufism aspects found within the pesantren’s poetry. To obtain reliable result, it puts emphasis on verstehen based on heurmenetical priciples developed by Paul Ricoeur, namely interpretation. The study finds that Sufism in the pesantren’s poetry deals with such number of symbols as light, flying, love, door, and prostration.